2012
DOI: 10.1111/j.1750-3841.2012.02990.x
|View full text |Cite
|
Sign up to set email alerts
|

True Density and Apparent Density During the Drying Process for Vegetables and Fruits: A Review

Abstract: This review presents the concepts involved in determining the density of foodstuffs, and summarizes the volumetric determination techniques used to calculate true density and apparent density in foodstuffs exposed to the drying process. The behavior of density with respect to moisture content (X) and drying temperature (T) is presented and explained with a basis in changes in structure, conformation, chemical composition, and second-order phase changes that occur in the processes of mass and heat transport, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 41 publications
2
26
0
1
Order By: Relevance
“…The significant similarity between particle and true density creates some confusion in interpretation. Despite the classical definition of true density as solid density, [2][3][4][5] some research publications [6][7][8][9] interpret true density as particle density. However, from the definition [Eq.…”
Section: Introductionmentioning
confidence: 99%
“…The significant similarity between particle and true density creates some confusion in interpretation. Despite the classical definition of true density as solid density, [2][3][4][5] some research publications [6][7][8][9] interpret true density as particle density. However, from the definition [Eq.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, at constant ultrasonication time and osmotic solution concentration, increasing immersion time from 60 to 240 min generally increased bulk density; however, this increase was not statistically significant (p [ 0.05). This phenomenon has been attributed to the increase in solids during the osmotic process [5]. Koc et al [3] also showed that osmotic dehydration pretreatment increased bulk density of quince during drying.…”
Section: Resultsmentioning
confidence: 96%
“…During drying, moisture transport is strongly affected by changes in structural properties. Thickness, the formation of channels, and pore distribution all represent a preferential path for moisture transport [5]. Bulk density is also of importance to food quality and, therefore, has significant impact on the consumer's choice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The buoyant force method for apparent volume determination is especially useful with solid objects that do not absorb liquid easily. [11] Since the shape of many fruits and vegetables resemble some regular geometrical objects, the use of theoretical estimation with certain numerical techniques can be used to estimate their volume. Sabliov et al [12] developed an image processing method for ellipsoidal agricultural products including eggs, lemons, limes, and peaches assuming that each product has an axisymmetric geometry and is a sum of superimposed elementary frustums.…”
Section: Introductionmentioning
confidence: 99%